Disease Mutation Study Identifies Critical Residues for Phosphatidylserine Flippase ATP11A - Sun, Kuanxiang (Biomed Res Int, 2020)
Phosphatidylserine flippase (P4-ATPase) transports PS from the outer to the inner leaflet of the lipid bilayer in the membrane to maintain PS asymmetry, which is important for biological activities of the cell. ATP11A is expressed in multiple tissues and plays a role in myotube formation. However, the detailed cellular function of ATP11A remains elusive. Mutation analysis revealed that I91, L308, and E897 residues in ATP8A2 are important for flippase activity. In order to investigate the roles of these corresponding amino acid residues in ATP11A protein, we assessed the expression and cellular localization of the respective ATP11A mutant proteins. ATP11A mainly localizes to the Golgi and plasma membrane when coexpressed with the β-subunit of the complex TMEM30A. Y300F mutation causes reduced ATP11A expression, and Y300F and D913K mutations affect correct localization of the Golgi and plasma membrane. In addition, Y300F and D913K mutations also affect PS flippase activity. Our data provides insight into important residues of ATP11A.